2010
DOI: 10.1124/jpet.110.165639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hyperlipidemia on Plasma Protein Binding and Hepatic Drug Transporter and Metabolic Enzyme Regulation in a Rat Model of Gestational Diabetes

Abstract: It is currently unknown whether gestational diabetes mellitus (GDM), a prevalent obstetrical complication, compounds the changes in drug disposition that occur naturally in pregnancy. Hyperlipidemia occurs in GDM. Using a rat model of GDM, we determined whether excess lipids compete with drugs for plasma protein binding. Because lipids activate nuclear receptors that regulate drug transporters and metabolic enzymes, we used proteome analysis to determine whether hyperlipidemia indirectly leads to the dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Although unbound serum concentrations were roughly equivalent in all of the groups, they represented a greater percentage of total serum concentrations in the GDM group. We have demonstrated previously that GDM-induced hyperlipidemia in rats, which was observed in this study (Table 1) and is observed clinically in GDM (Wiznitzer et al, 2009), leads to drug displacement (Anger and Piquette-Miller, 2010). Albumin concentrations in GDM also were reduced significantly, which means there were fewer LPV binding sites.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Although unbound serum concentrations were roughly equivalent in all of the groups, they represented a greater percentage of total serum concentrations in the GDM group. We have demonstrated previously that GDM-induced hyperlipidemia in rats, which was observed in this study (Table 1) and is observed clinically in GDM (Wiznitzer et al, 2009), leads to drug displacement (Anger and Piquette-Miller, 2010). Albumin concentrations in GDM also were reduced significantly, which means there were fewer LPV binding sites.…”
Section: Discussionmentioning
confidence: 47%
“…Induction of Mdr1 and Cyp3a has been observed in tissues from male rats with STZ-induced diabetes (Maeng et al, 2007;Kameyama et al, 2008;Hasegawa et al, 2010), but reports in female rats with STZ-induced diabetes or STZ-induced GDM are limited (Mulay and Varma, 1984;Anger et al, 2009;Anger and Piquette-Miller, 2010). We posit that disruptions to lipid and glucose homeostasis underlie the alterations to drug transporter and Cyp3a2 expression that were observed in STZ-induced GDM.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations